Antimicrobial activity of brown propolis ethanolic extract and its application in intramammary formulation for the treatment of bovine mastitis - Valdenice Félix da Silva; Danillo Sales Rosa; Priscila Izidro de Figueirêdo; Tania Maria Sarmento da Silva; Rodolfo de Moraes Peixoto; Mateus Matiuzzi da Costa (Brazilian Journal of Microbiology, 2026)

Enhancing mineral supply chain resilience in the Global South: insights from the natural zeolite sector - Jessica Costa Cruz; Charbel Jose Chiappetta Jabbour; Rodolfo Leandro de Faria Olivo; Cristina Lourenço Ubeda (Resources Policy, 2026)

Fruit Quality of Passiflora Cincinnata at Different Ripening Stages Under Irrigated and Rainfed Cultivation - Giuliana Naiara Barros Sales; Marília Hortência Batista Silva Rodrigues; Toshik Iarley da Silva; Rodolfo Rodrigo de Almeida Lacerda; Josélio dos Santos da Silva; Daniel da Conceição Almeida; Ana Clara Farias Siqueira; Walter Esfrain Pereira; Pahlevi Augusto de Souza; Genilson Lima Diniz; Saint Clair Lira Santos; Geovani Soares de Lima; et al. (Applied Fruit Science, 2026)

Early Detection of Soil Multifunctionality Loss in Amazonian Mangroves Driven by Land Use Change - Fellipe A. O. Mello; Tiago O. Ferreira; Francisco Ruiz; Rodolfo F. Costa; Hermano M. Queiroz; Danilo C. Mello; Rafael B. Menillo; Lorena M. Barbosa; Angelo F. Bernardino; Maurício R. Cherubin (Wetlands, 2026)
Mangroves are a vital ecosystem for coastal biodiversity and climate regulation but face increasing pressure from agriculture and aquaculture expansion. These threats promote high levels of degradation from direct land use change and hidden impacts from aquaculture effluents rich in nitrogen, phosphorus, and organic compounds. We developed a soil health index to detect different stages of mangrove ecosystem degradation by incorporating the concept of soil multifunctionality within a site-specific environmental context. We applied this index to four mangrove areas in the Amazon coast under different land uses: pristine mangroves, mangroves adjacent to shrimp farms, mangroves converted to shrimp farms and converted to pasture. Pristine mangroves are functioning by 67% of their full capacity into ecosystem boundaries, while pristine mangroves near shrimp farms are functioning by 64%, a sign of early degradation detection. Mangroves converted to shrimp farms are functioning by 52%, and, finally, those converted to pasture by 32%. A large soil dataset of eight indicators was required to detect an early stage of degradation in the mangroves adjacent to shrimp farms, while for the advanced degradation cases of shrimp farms and pasture only three indicators were able to detect the loss of soil multifunctionality. Converting mangroves to human-focused food production systems do not offer reasonable trade-offs to justify land exploration, since the converted sites reduced the delivery of ecosystem services to less than 30%. The index represents an effective alternative for surveying and monitoring degradation stages and ecosystem service losses in mangroves under land-use change.

Recombinant FSH as an alternative to pituitary-extracted FSH for superovulation and embryo production in sheep - Brenda B. Martins; Aline Matos Arrais; Pedro Henrique Nicolau Pinto; Maria Paula da Costa Plaza; Pedro Henrique de Mello Cotta Maia; Sandra Ribeiro da Silva; Joanna M.G. Souza-Fabjan; Alejo Menchaca; Rodolfo Ungerfeld; Jeferson Ferreira da Fonseca; Felipe Zandonadi Brandão (Animal Reproduction Science, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

In silico and in vitro assessment of the eucalyptus wood vinegar impact on reproduction of ticks Rhipicephalus microplus (Acari: Ixodidae) - Ana Karolinne de Alencar França; Alexandre Santos Pimenta; Yandra Thais Rocha da Mota; Pablo Leandro Filgueira Feitosa; Ana Carolyna Diógenes Bezerra; Thays Vieira da Costa Monteiro; Maíra Fasciotti; Rafael Rodolfo de Melo; Lúcio César Dantas de Medeiros; Ana Carla Diógenes Suassuna Bezerra (Veterinary Parasitology, 2026)

Continued loss of mangrove carbon stocks six years after a climate impact in SE Brazil - Carla F.O. Pacheco; Rodolfo F. Costa; Antonio Elves B. Silva; Daniela Y. Gaurisas; Tiago O. Ferreira; Angelo F. Bernardino (Forest Ecology and Management, 2026)

Intestinal parasites in dogs and their association with clinical manifestations of canine visceral leishmaniasis - Allan de Jesus Mendonça Severino; Dharliton Soares Gomes; André Tetzl Costa; Maykelin Fuentes Zaldívar; Nathália Moreira Teodoro de Oliveira; Bianca Leal de Oliveira; Paulo Ricardo Silva Coelho; Felipe Bisaggio Pereira; Paulo Ricardo de Oliveira Paes; João Carlos França-Silva; Rodolfo Cordeiro Giunchetti; Stefan Michael Geiger (Veterinary Parasitology, 2026)

Coupled effect of pyrolysis temperature and HNO3 pretreatment on sugarcane bagasse fast pyrolysis for levoglucosan production - Geraldo Ferreira David; Rodolfo Roberto Moreno-Parra; Victor Haber Perez; Thays da Costa Silveira; Euripedes Garcia Silveira Junior; Oselys Rodriguez Justo; Manuel Garcia-Perez (Biomass and Bioenergy, 2025)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Recombinant bovine somatotropin alters embryonic gene expression in superovulated ewes - Ana Paula Pereira Schmidt; Pedro Henrique Nicolau Pinto; Juan Pedro Bottino González; Pedro Henrique de Mello Cotta Maia; Maria Paula da Costa Plaza; Brenda Barbosa Martins; Ribrio Ivan Tavares Pereira Batista; Joanna Maria G. Souza-Fabjan; Mário Felipe Alvarez Balaro; Jeferson Ferreira da Fonseca; Rodolfo Ungerfeld; Felipe Zandonadi Brandão (Animal Reproduction Science, 2025)

Pharmacological potential of Euphorbia tirucalli L. latex in gastric adenocarcinoma: from an ethnopharmacological perspective into new products - Larissa Silva de Souza; Cristina Luz Tosta; Bárbara Costa Lemos; Regina Westphal; Jorge Welton de Souza Pina; Jéssica Rodrigues Pereira de Oliveira Borlot; Rodolfo Goetze Fiorot; Anne Caroline de Cândido Gomes; Rodrigo Rezende Kitagawa; Sandro José Greco; Paulo Roberto Filgueiras; Ricardo Machado Kuster (Natural Product Research, 2025)

Toxicogenic effects of yttrium oxide nanoparticles on Allium cepa root tip meristem cells - Mylena Boeque Lascola; Kristian Rodolfo Santos; Sara Nascimento dos Santos; Francielen Barroso Aragão; Iara da Costa Souza; Marisa Narciso Fernandes; Silvia Tamie Matsumoto (Environmental Science and Pollution Research, 2025)

Exploring nutritional and bioactive properties of Maranta arundinacea L.: An unconventional food plant - Yasmine Fernandes Oliveira; Rodolfo Dantas Lima Junior; Jorge Luiz Souza Simão; Tiago Dias; Tânia Aparecida Pinto de Castro Ferreira; Maurício Vicente Cruz; Kátia Flávia Fernandes; Marco Aurélio Sperança; Fabiola Manhas Verbi Pereira; Edenir Rodrigues Pereira-Filho; Larissa Silva Costa; Patricia Santos Lopes; et al. (Food Research International, 2025)

Effect of supplemented diet on the kinetic profile of polystyrene biodegradation by Tenebrio molitor larvae: Physical, chemical, thermal, wettability and zeta potential measurements - Camila Bebber; Bruna Trombotto; Guilherme Eccard Rezende da Cunha; Rodolfo Debone Piazza; Giovana Sant´Ana Pegorin-Brasil; Josana Carla Silva Sasaki; Rogério Penna Gonçalves; Lindomar Soares dos Santos; Rodrigo Fernando Costa Marques; Cassamo Ussemane Mussagy; Rosana Goldbeck; Wei Cao; et al. (Journal of Environmental Chemical Engineering, 2025)

Multivariate optimization of the infrared radiation-assisted digestion of bivalve mollusk samples from Brazil for arsenic and trace metals determination using ICP OES - Giovanna Carneiro Costa; Allana Sobrinho dos Santos; Rennan G.O. Araujo; Maria Graças A. Korn; Rodolfo M.M. Santana (Food Chemistry, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Coastal natural products: a review applied to antimycobacterial activity - Rodolfo Moreira Baptista; Marcos Alaniz Rodrigues; Fabio Roselet; César Serra Bonifácio Costa; Pedro Eduardo Almeida da Silva; Daniela Fernandes Ramos (Natural Product Research, 2025)

Cellular and biochemical alterations induced by diesel oil in the brown alga Sargassum cymosum var. stenophyllum cultured in vitro - Eva Regina Oliveira; Fernanda Ramlov; Éder Carlos Schmidt; Débora Tomazi; Claudia Marlene Bauer; Fernanda K. Pilatti; Rodolfo Moresco; Giulia Burle Costa; Sara Cardoso; Zenilda Laurita Bouzon; Paulo Antunes Horta; Miguel Rocha; et al. (Chemosphere, 2025)

Population size, income and poor sanitation interact to explain widespread streamwater contamination by antidepressants in the Metropolitan Region of São Paulo - Luis Schiesari; Ricardo Taniwaki; Rodolfo Mei Pelinson; Hagop Armenio Barsoumian; Giulia Baldaconi Bispo; Gabriel Lourenço Brejão; Mayumi Cursino de Moura Hirye; Aline Franco Martins; José Luiz Costa (Environmental Pollution, 2025)

Evaporating temperature estimation of refrigeration systems based on vibration data-driven soft sensors - Ahryman Seixas Busse de Siqueira Nascimento; João Paulo Zomer Machado; Leandro dos Santos Coelho; Rodolfo César Costa Flesch (International Journal of Refrigeration, 2024)

Soil greenhouse gas fluxes partially reduce the net gains in carbon sequestration in mangroves of the Brazilian Amazon - Angelo F. Bernardino; Hermano M. Queiroz; Gabriel N. Nobrega; Gabriel C. Coppo; Christian J. Sanders; Antonio E.B. Silva; J. Boone Kauffman; Rodolfo F. Costa; Carla F. Pacheco; André Vassoler; Araiene P. Pereira; Francisco Ruiz; et al. (Environmental Research, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Cytogenetic and photosynthetic responses of plants after exposure to water from a lake environment - Ian Drumond Duarte; Edvar Júnior Roncetti Coelho; Livia Dorsh Rocha; Mariana Morozesk; Marina Marques Bonomo; Iara da Costa Souza; Liliane Baldan Zani; Iasmini Nicoli Galter; Natalia Nati; Sara Nascimento dos Santos; Kristian Rodolfo Santos; Francielen Barroso Aragão; et al. (Environmental Science and Pollution Research, 2024)

Comprehensive analysis of biochemical compounds, chemical elements and metabolites modifications in maize plants infected with maize rayado fino virus (MRFV) - Marcos Vinicius Silva de Andrade; Magda Alana Pompelli Manica; Maria do Carmo Costa Silva; Roberto Venceslau de Carvalho; Rodolfo Vargas Castilhos; Antonio Gilberto Ferreira; Maria Cristina Canale (Physiological and Molecular Plant Pathology, 2024)

Continental subduction and exhumation of the lower crust in a hot orogen: Insights from high-pressure (ultra) high-temperature granulite in the Pouso Alto Nappe, Southeast Brazil - Beatriz Benetti; Mario da Costa Campos Neto; Rodolfo Carosi; Salvatore Iaccarino; George Luiz Luvizotto; Chiara Montomoli; Antonio Langone (Lithos, 2024)

Isolated and grouped relationships between type 2 diabetes and peripheral arterial disease on skin temperature in the foot plantar region - Raschelle Ramalho Rosas; Francisco Thalyson Moraes Silveira; Rhuan Valerio Cavalcante Quintela; Rafael Martins da Costa; Inês Amanda Streit; Rodolfo André Dellagrana; Mateus Rossato (Journal of Thermal Biology, 2024)

Phytopharmacological aspects of Mimosa tenuiflora (Willd.) poir.: a systematic review of preclinical data - Emerson de Oliveira Silva; Myla Lôbo de Souza; Nathália Andrezza Carvalho de Souza; Demis Ferreira de Melo; Lucas Amadeu Gonzaga da Costa; Bruna Fernanda de Lima Arruda Holanda; Rodolfo Hideki Vicente Nishimura; Larissa Araújo Rolim; Pedro José Rolim Neto (Phytochemistry Reviews, 2024)

Sedimentary facies and palynoflora of the Andirá and Arari formations in the Autazes region, Amazonas Basin - Ziomar Costa e Silva Junior; Emílio Alberto Amaral Soares; Rodolfo Dino; Luzia Antonioli (Journal of South American Earth Sciences, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Treatment of subclinical mastitis in dairy goats experimentally infected with Staphylococcus aureus using natural therapeutic protocol - Matheus Rodrigues de Souza; Aldri Éderson Vila Nova Silva; Renata de Faria Silva Souza; Antonio Wilton Cavalcante Fernandes; Rodolfo de Moraes Peixoto; Danillo Sales Rosa; Ianka Fernanda da Silva Soares; Mateus Matiuzzi da Costa (Tropical Animal Health and Production, 2024)

Assessment of the ecological quality status of the Sepetiba Bay (SE Brazil): When metabarcoding meets morphology on foraminifera - Fabrício Leandro Damasceno; Maria Virgínia Alves Martins; Fabrizio Frontalini; Jan Pawlowski; Kristina Cermakova; Inès Barrenechea Angeles; Luiz Guilherme Costa Santos; João Graciano Mendonça Filho; Fabio Francescangeli; Thaise M. Senez-Mello; Wellen Fernanda Louzada Castelo; Renata Cardia Rebouças; et al. (Marine Environmental Research, 2024)

The impacts of digital transformation on fisheries policy and sustainability: Lessons from Timor-Leste - Alexander Tilley; Rodolfo Dam Lam; Denise Lozano Lazo; Joctan Dos Reis Lopes; Dede Freitas Da Costa; Maria De Fátima Belo; Joaquina Da Silva; Gilberto Da Cruz; Cristiano Rossignoli (Environmental Science & Policy, 2024)

Isolation and primary culture of human abdominal aorta smooth muscle cells from brain-dead donors: an experimental model for vascular diseases - Carlos Alexandre Curylofo Corsi; Claudia Tarcila Gomes Sares; Fabiola Mestriner; Jéssyca Michelon-Barbosa; Vinicius Flora Dugaich; Timna Varela Martins; Alex Martins Násare; Roberta Ribeiro Costa Rosales; Maria Cecília Jordani; José Carlos Alves-Filho; Rodolfo Borges dos Reis; Mauricio Serra Ribeiro; et al. (Cell and Tissue Banking, 2024)

In-sequence tectonic evolution of Ediacaran nappes in the southeastern branch of the Brasília Orogen (SE Brazil): Constraints from metamorphic iterative thermodynamic modeling and monazite petrochronology - Beatriz Benetti; Mario da Costa Campos Neto; Rodolfo Carosi; George Luvizotto; Salvatore Iaccarino; Chiara Montomoli (Lithos, 2024)

Reproductive seasonality of hair rams under tropical conditions: an alternative for non-seasonal lamb production? - Arnaldo de Sá Geraldo; Pedro Henrique Nicolau Pinto; Ana Beatriz da Silva Carvalho; Marta Maria Campos Pereira da Costa; Juliana Dantas Rodrigues Santos; Augusto Ryonosuke Taira; Isabel Oliveira Cosentino; Bruna Ramalho Rigaud de Figueiredo; Mário Felipe Alvarez Balaro; Rodolfo Ungerfeld; Felipe Zandonadi Brandão (Tropical Animal Health and Production, 2024)

Reproductive Cycle of the Sea Urchin Paracentrotus lividus (Lamarck, 1816) on the Central West Coast of Portugal: New Perspective on the Gametogenic Cycle - Andreia Raposo; Susana M. F. Ferreira; Rodolfo Ramos; Catarina Anjos; Sílvia C. Gonçalves; Pedro M. Santos; Teresa Baptista; José L. Costa; Ana Pombo (Journal of Marine Science and Engineering, 2023)
A population of sea urchins, Paracentrotus lividus, from the central west coast of Portugal was studied to characterise their reproductive biology and possible relationships with environmental factors. An annual gametogenic cycle was found, with a broad spawning season, from May to November, according to a relatively synchronous gamete maturation process. Depending on the environmental factors (temperature, photoperiod), two separate periods could be distinguished, with more individuals maturing and spawning at the same time. When this happened, the first event evolved when temperature rose to a critical point, and the second occurred afterwards, when temperature decreased significantly. Notwithstanding, it was found that individuals matured later than previously described for other populations (e.g., north of Portugal), mostly in late spring, with a higher gonadosomatic index in May. A new classification scale was proposed for identifying the stages of P. lividus gametogenic cycle, based on new findings. It contributed to its simplification and easier comprehension. This study provides useful information for a differentiated sustainable management of P. lividus, according to local conditions. Establishing a closed harvesting season might be considered, based on the differences observed between Portuguese populations and other European ones.

Serological profile of respiratory viruses in unvaccinated steers upon their arrival at Brazilian feedlot facilities - Larissa Melo Chicoski; Juliana Torres Tomazi Fritzen; Elis Lorenzetti; Arthur Roberto da Costa; Elio Moro; Everton Rodolfo de Carvalho; Alice Fernandes Alfieri; Amauri Alcindo Alfieri (Brazilian Journal of Microbiology, 2023)

Environmental magnetic characterization for the Pialli Level and the Cretaceous Oceanic Red Bed 7 (late Albian, Poggio le Guaine core, central Italy) - Kathlem M. Teixeira; Jairo F. Savian; Raquel G. Mello; Carolina G. Leandro; Marcus V.L. Kochhann; Martino Giorgioni; Paula Harethusa Pereira Costa Vidal; Ana P. de Martini; Luigi Jovane; Fabrizio Frontalini; Rodolfo Coccioni; Milene Figueiredo; et al. (Global and Planetary Change, 2023)

Occurrence of extended‐spectrum β‐lactamases‐producing Escherichia coli isolates over gradient pollution in an urban tropical estuary - Wellington Felipe Costa; Rodolfo Paranhos; Marianne Pataro Mello; Renata Cristina Picão; Marinella Silva Laport (Environmental Microbiology, 2023)
Bacterial resistance to antimicrobials is a global public health problem that surpasses the human context and can be increased by pollution. However, the lack of systematic monitoring of resistance in some aquatic matrices, such as tropical estuaries, makes it unknown whether its occurrence is associated with anthropogenic pollution in these environments. Therefore, we investigated the occurrence of extended‐spectrum beta‐lactamases (ESBLs) producing Escherichia coli as a resistance indicator for 12 consecutive months at three representative points of a pollution gradient in Guanabara Bay (GB), Brazil. Sixty‐six E. coli strains were selected from 72 samples of GB waters in the presence of ceftriaxone (8 μg mL −1 ) and identified by MALDI‐TOF MS. Of the 66, 55 (83.3%) strains were ESBL producers. They carried beta‐lactamase/ESBL genes, with the predominance of bla CTX‐M (54, 98.2%), especially the bla CTX‐M‐1,2 allele (49.1%). These strains were detected frequently (81.8%) from the point with the highest pollution levels. Furthermore, the marker for Class 1 integron, intI1 gene, was detected in 54.5% of ESBL producers. These data suggest an association between antimicrobial‐resistant E. coli and sewage pollution in aquatic environments raising concerns about the possible risks of human exposure to these waters and fish consumption.

Alkylamides from Acmella oleracea : antinociceptive effect and molecular docking with cannabinoid and TRPV1 receptors - Raíssa M. Kao Yien; Anne Caroline C. Gomes; Rodolfo Goetze Fiorot; Ana Luísa Palhares Miranda; Gilda A. Neves; Brenda da Silva Andrade; Fernanda N. Costa; Jorge Luiz Mendonça Tributino; Naomi Kato Simas (Natural Product Research, 2023)

Moisture, temperature and respiration of two soil classes under pasture and tropical dry forest in the semiarid Brazilian region - José Romualdo de Sousa Lima; Rodolfo Marcondes Silva Souza; Everardo Valadares de Sá Barreto Sampaio; Antônio Celso Dantas Antonino; Eduardo Soares de Souza; Érika Valente de Medeiros; Gustavo Pereira Duda; Carlas Renata Prissila Costa Ferreira; Rômulo Simões César Menezes; Claude Hammecker (Journal of Arid Environments, 2023)

Antimicrobial activity and chemical profile of wood vinegar from eucalyptus (Eucalyptus urophylla x Eucalyptus grandis - clone I144) and bamboo (Bambusa vulgaris) - Gil Sander Próspero Gama; Alexandre Santos Pimenta; Francisco Marlon Carneiro Feijó; Caio Sérgio Santos; Bruno Caio Chaves Fernandes; Moacir Franco de Oliveira; Elias Costa de Souza; Thays V. C. Monteiro; Maíra Fasciotti; Tatiane Kelly Barbosa de Azevedo; Rafael Rodolfo de Melo; Ananias Francisco Dias Júnior (World Journal of Microbiology and Biotechnology, 2023)

Soil Chemical Properties, Enzyme Activity and Soybean and Corn Yields in a Tropical Soil Under No-till Amended with Lime and Phosphogypsum - Rodolfo F. Costa; Ruan F. Firmano; João W. Bossolani; Luís R. F. Alleoni (International Journal of Plant Production, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Relationship between different sources of non-protein nitrogen and supplementation times on performance and metabolism of grazing Nellore cattle during the dry season - Verônica A. C. Mota; Laura F. Prados; Keuven S. Nascimento; Rodolfo. M. Fernandes; Luiz F. Costa e Silva; Vaughn B. Holder; James E. Pettigrew; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Genetic diversity and structure of an endangered medicinal plant species (Pilocarpus microphyllus) in eastern Amazon: implications for conservation - Waleria Pereira Monteiro; Jeronymo Dalapicolla; Carolina Silva Carvalho; Jamille Costa Veiga; Santelmo Vasconcelos; Silvio Junio Ramos; Markus Gastauer; Rodolfo Jaffé; Cecílio Frois Caldeira (Conservation Genetics, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

A novel monitoring protocol to evaluate large-scale forest restoration projects in the tropics - Ciro José Ribeiro de Moura; Maria Fernanda Santos Quintela da Costa Nunes; Rodolfo Cesar Real de Abreu (Tropical Ecology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Modelling of BCS1L-related human mitochondrial disease in Drosophila melanogaster - Michele Brischigliaro; Elena Frigo; Samantha Corrà; Cristiano De Pittà; Ildikò Szabò; Massimo Zeviani; Rodolfo Costa (Journal of Molecular Medicine, 2021)
Mutations in BCS1L are the most frequent cause of human mitochondrial disease linked to complex III deficiency. Different forms of BCS1L -related diseases and more than 20 pathogenic alleles have been reported to date. Clinical symptoms are highly heterogenous, and multisystem involvement is often present, with liver and brain being the most frequently affected organs. BCS1L encodes a mitochondrial AAA + -family member with essential roles in the latest steps in the biogenesis of mitochondrial respiratory chain complex III. Since Bcs1 has been investigated mostly in yeast and mammals, its function in invertebrates remains largely unknown. Here, we describe the phenotypical, biochemical and metabolic consequences of Bcs1 genetic manipulation in Drosophila melanogaster. Our data demonstrate the fundamental role of Bcs1 in complex III biogenesis in invertebrates and provide novel, reliable models for BCS1L- related human mitochondrial diseases. These models recapitulate several features of the human disorders, collectively pointing to a crucial role of Bcs1 and, in turn, of complex III, in development, organismal fitness and physiology of several tissues.

Biochar as a strategy to manage plant diseases caused by pathogens inhabiting the soil: a critical review - Erika Valente de Medeiros; Neyla Thayná Lima; José Romualdo de Sousa Lima; Kedma Maria Silva Pinto; Diogo Paes da Costa; Cícero Luiz Franco Junior; Rodolfo Marcondes Silva Souza; Claude Hammecker (Phytoparasitica, 2021)

Floating aquatic macrophytes for the treatment of aquaculture effluents - Vera Mônica de Vasconcelos; Elís Regina Costa de Morais; Samantha Joyce Bezerra Faustino; Maria Carolina Ramirez Hernandez; Hiara Ruth da Silva Câmara Gaudêncio; Rafael Rodolfo de Melo; Ambrósio Paula Bessa Junior (Environmental Science and Pollution Research, 2021)

Holoplankton and meroplankton of three western Atlantic sedimentary basins - Cristina de Oliveira Dias; Ana Cristina Teixeira Bonecker; Márcia Salustiano de Castro; Pedro Freitas de Carvalho; Rodolfo Paranhos; Sérgio Luiz Costa Bonecker (Marine Biology Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Different approaches for modeling Swietenia macrophylla commercial volume in an Amazon agroforestry system - Cícero Jorge Fonseca Dolácio; Thiago Wendling Gonçalves de Oliveira; Rudson Silva Oliveira; Clebson Lima Cerqueira; Luiz Rodolfo Reis Costa (Agroforestry Systems, 2020)

Physical–mechanical properties of wood panel composites produced with Qualea sp. sawdust and recycled polypropylene - Daiane Cristina Lima; Rafael Rodolfo de Melo; Alexandre Santos Pimenta; Talita Dantas Pedrosa; Maila Janaína Coelho de Souza; Elias Costa de Souza (Environmental Science and Pollution Research, 2020)

Effects of Roughness Loss on Reef Hydrodynamics and Coastal Protection: Approaches in Latin America - Juan D. Osorio-Cano; Juan C. Alcérreca-Huerta; Ismael Mariño-Tapia; Andrés F. Osorio; Cesar Acevedo-Ramírez; Cecilia Enriquez; Mirella Costa; Pedro Pereira; Edgar Mendoza; Mireille Escudero; Alejandro Astorga-Moar; José López-González; et al. (Estuaries and Coasts, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Evaluation of the impact caused by handling procedures on the embryonic development of the sea urchin Paracentrotus lividus (Lamarck, 1816) - Rodolfo Ramos; Andreia Raposo; Sílvia Gonçalves; Teresa Baptista; José Lino Costa; Ana Pombo; Susana M.F. Ferreira (Frontiers in Marine Science, 2018)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Effect of supplementation of beef cattle with different protein levels and degradation rates during transition from the dry to rainy season - Rodolfo Maciel Fernandes; Chafic Mustafé de Almeida; Bruna Caldas Carvalho; João Alexandrino Alves Neto; Verônica Aparecida Costa Mota; Flávio Dutra de Resende; Gustavo Rezende Siqueira (Tropical Animal Health and Production, 2016)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

X-Chromosome STR markers data in a Cabo Verde immigrant population of Lisboa - Heloísa Afonso Costa; Paulo Morais; Cláudia Vieira da Silva; Sara Matos; Rodolfo Marques Santos; Rosa Espinheira; Jorge Costa Santos; António Amorim (Molecular Biology Reports, 2014)

Estimating the Density of Honeybee Colonies across Their Natural Range to Fill the Gap in Pollinator Decline Censuses - RODOLFO JAFFÉ; VINCENT DIETEMANN; MIKE H. ALLSOPP; CECILIA COSTA; ROBIN M. CREWE; RAFFAELE DALL’OLIO; PILAR DE LA RÚA; MOGBEL A. A. EL‐NIWEIRI; INGEMAR FRIES; NIKOLA KEZIC; MICHAEL S. MEUSEL; ROBERT J. PAXTON; et al. (Conservation Biology, 2010)
Although pollinator declines are a global biodiversity threat, the demography of the western honeybee ( Apis mellifera ) has not been considered by conservationists because it is biased by the activity of beekeepers. To fill this gap in pollinator decline censuses and to provide a broad picture of the current status of honeybees across their natural range, we used microsatellite genetic markers to estimate colony densities and genetic diversity at different locations in Europe, Africa, and central Asia that had different patterns of land use. Genetic diversity and colony densities were highest in South Africa and lowest in Northern Europe and were correlated with mean annual temperature. Confounding factors not related to climate, however, are also likely to influence genetic diversity and colony densities in honeybee populations. Land use showed a significantly negative influence over genetic diversity and the density of honeybee colonies over all sampling locations. In Europe honeybees sampled in nature reserves had genetic diversity and colony densities similar to those sampled in agricultural landscapes, which suggests that the former are not wild but may have come from managed hives. Other results also support this idea: putative wild bees were rare in our European samples, and the mean estimated density of honeybee colonies on the continent closely resembled the reported mean number of managed hives. Current densities of European honeybee populations are in the same range as those found in the adverse climatic conditions of the Kalahari and Saharan deserts, which suggests that beekeeping activities do not compensate for the loss of wild colonies. Our findings highlight the importance of reconsidering the conservation status of honeybees in Europe and of regarding beekeeping not only as a profitable business for producing honey, but also as an essential component of biodiversity conservation.

Post-transcriptional silencing of the Drosophila homolog of human ZASP: a molecular and functional analysis - Clara Benna; Samantha Peron; Giorgia Rizzo; Georgine Faulkner; Aram Megighian; Giuliana Perini; Giuseppe Tognon; Giorgio Valle; Carlo Reggiani; Rodolfo Costa; Mauro A. Zordan (Cell and Tissue Research, 2009)

Archaeal and bacterial communities of heavy metal contaminated acidic waters from zinc mine residues in Sepetiba Bay - Welington I. Almeida; Ricardo P. Vieira; Alexander Machado Cardoso; Cynthia B. Silveira; Rebeca G. Costa; Alessandra M. Gonzalez; Rodolfo Paranhos; João A. Medeiros; Flávia A. Freitas; Rodolpho M. Albano; Orlando B. Martins (Extremophiles, 2009)

Conservation value of an exotic species: the case of coconuts on the Kayapo indigenous lands, south-eastern Amazonia - Rodolfo Salm; Lisa Feder; Mario Augusto Gonçalves Jardim; Nefertiti Hass; Euphly Jalles-Filho; Ana Maria Costa (Environment, Development and Sustainability, 2009)

RNA interference: ready to silence cancer? - Simone Mocellin; Rodolfo Costa; Donato Nitti (Journal of Molecular Medicine, 2006)

Molecular Analysis of Circadian Clocks in Drosophila simulans - Anthony S. Rogers; Ezio Rosato; Rodolfo Costa; Charalambos P. Kyriacou (Genetica, 2004)

Esterase-6 allozymes: Biochemical studies of two common and one rare variant inDrosophila melanogaster - Rodolfo Costa; Loredana Nigro; Gian Antonio Danieli (Biochemical Genetics, 1983)